IMPACT & TREATMENT OF NON-MOTOR SYMPTOMS IN EARLY PARKINSON'S DISEASE. Issue 11 (14th October 2015) - Baig, Fahd; Lawton, Michael; Rolinski, Michal; Ruffmann, Claudio; Nithi, Kannan; Evetts, Samuel; Fernandes, Hugo; Ben-Shlomo, Yoav; Hu, Michele
Abstract : Objective: To delineate treatment and quality of life of non-motor symptoms (NMS) in early Parkinson's disease (PD) and first-degree relatives. Background: Non-motor symptoms (NMS) are an important prodromal feature of Parkinson's disease (PD). However, their frequency, treatment rates and impact on health-related quality of life (HRQoL) in the early motor phase is unclear. Methods: 769 population-ascertained PD subjects within 3.5 years of diagnosis and 287 control subjects were assessed. Validated severity questionnaires were employed to assess NMS symptoms across the following domains: (1) neuropsychiatric (2) gastrointestinal (3) sleep (4) sensory (5) autonomic (6) sexual. Health related quality of life (HRQoL), functional status and management were also evaluated. Results: NMS were common in early PD. More than half of the PD cases had hyposmia, pain, fatigue, sleep disturbance or urinary dysfunction. PD cases had worse HRQoL scores than controls (OR 4.1, p<0.001) with depression, anxiety and pain being stronger drivers than MDS-UPDRS motor scores. Quality of life is affected in early PD, although 23% of participants reported no problems. NMS were rarely treated in routine clinical practice. Conclusions: Despite their major impact on HRQoL, NMS are usually under-recognised and treated. The use of screening tools could improve recognition and treatment of NMS in early PD.